A Call to Action to Address the Burden of Cardiovascular Disease in People with Diabetes. Issue 1 (19th December 2022) - Lorenty, Karolay; Harding, Ed; Fenton, Olive
In 2022, the Global Heart Hub held a Cardio-Diabetes Think Tank to develop consensus on actions that need to be taken to address the growing burden of diabetes and cardiovascular disease (CVD). Across the world, diabetes affects almost half a billion people, who have a twofold increased risk of CVD. The patient-led think tank brought together the diabetes and CVD communities, with representatives from leading global and regional patient and professional organisations, and produced a report outlining tangible and specific actions that reflect what matters most to patients. The think tank calls for key players in both communities to work together to implement these actions, putting people at the centre of decision-making and improving cardio-diabetes care.